Blood flow restriction training in clinical musculoskeletal rehabilitation: a systematic review and meta-analysis. Issue 13 (4th March 2017) - Hughes, Luke; Paton, Bruce; Rosenblatt, Ben; Gissane, Conor; Patterson, Stephen David
Abstract : Background and objective: Low-load exercise training with blood flow restriction (BFR) can increase muscle strength and may offer an effective clinical musculoskeletal (MSK) rehabilitation tool. The aim of this review was to systematically analyse the evidence regarding the effectiveness of this novel training modality in clinical MSK rehabilitation. Design: This is a systematic review and meta-analysis of peer-reviewed literature examining BFR training in clinical MSK rehabilitation (Research Registry; researchregistry91). Data sources: A literature search was conducted across SPORTDiscus (EBSCO), PubMed and Science Direct databases, including the reference lists of relevant papers. Two independent reviewers extracted study characteristics and MSK and functional outcome measures. Study quality and reporting was assessed using the Tool for the assEssment of Study qualiTy and reporting in EXercise. Eligibility: Search results were limited to exercise training studies investigating BFR training in clinical MSK rehabilitation, published in a scientific peer-reviewed journal in English. Results: Twenty studies were eligible, including ACL reconstruction (n=3), knee osteoarthritis (n=3), older adults at risk of sarcopenia (n=13) and patients with sporadic inclusion body myositis (n=1). Analysis of pooled data indicated low-load BFR training had a moderate effect on increasing strength (Hedges' g=0.523, 95% CI 0.263 to 0.784, p<0.001), but was less effective than heavy-load training (Hedges' g=0.674, 95% CI 0.296 to 1.052, p<0.001). Conclusion: Compared with low-load training, low-load BFR training is more effective, tolerable and therefore a potential clinical rehabilitation tool. There is a need for the development of an individualised approach to training prescription to minimise patient risk and increase effectiveness.